Comparative efficiency of carbohydrates on the biofilm‐forming ability of enteroaggregative Escherichia coli. Issue 3 (9th February 2022) - Pathak, Richa; Vergis, Jess; Chouhan, Garima; Kumar, Manesh; Malik, Satyaveer Singh; Barbuddhe, Sukhadeo Baliram; Rawool, Deepak Bhiwa
Abstract: The biofilm‐forming ability of microbes is often correlated with drug resistance; however, this association among enteroaggregative Escherichia coli (EAEC) strains remains naïve. Moreover, the investigations exploring uptake and assimilation of sugars either qualitatively or quantitatively by the biofilm‐forming EAEC strains have not yet been documented. Hence, this study investigated the role of various categories of sugars (monosaccharides, disaccharides, and polysaccharide) on the biofilm‐forming ability of three each of multi‐drug‐resistant (MDR) as well as non‐MDR typical EAEC strains. The EAEC strains exhibited black colonies on congo red agar (CRA) with monosaccharides and disaccharides, whereas all the strains exhibited red colonies on CRA with the polysaccharide. Although significant ( p < 0.001) biofilm‐forming ability was observed by all the EAEC strains in sugar‐dependent microtiter plate assay, color change from pink to orange and yellow was noticed in presence of monosaccharides and disaccharide, while absent in polysaccharides. Besides, significantly higher bacterial counts were observed in presence of monosaccharides and disaccharides ( p < 0.01); however, such significant bacterial counts were not noticed with the polysaccharide. Further, the real‐time PCR data exhibited comparatively higher relative expression of biofilm‐associated fis gene among EAEC strains grown in presence of monosaccharides, followed by disaccharide and polysaccharide, respectively that concurred with the flow cytometry data. No significant ( p > 0.05) difference was observed in the biofilm‐forming ability between MDR‐ and non‐MDR EAEC strains. This study illustrated the role of carbohydrates on the biofilm‐forming ability of EAEC and warranted utmost attention concerning the usage of carbohydrates in food processing industries, for its incorporation as functional food additives. Abstract : This study investigated the role of different sugar types on the biofilm formation of typical enteroaggregative Escherichia coli (EAEC). The monosaccharide (D‐Glucose) promoted biofilm formation of EAEC strains in comparison with the disaccharide (sucrose) and polysaccharide (starch) and demands attention for the use of carbohydrates as functional food additives.